Knowledge, Attitudes, and Perspectives on the Use of Artificial Intelligence in the Future Healthcare Workforce - Özlem GÖK (VITALIS JOURNAL, 2026)
This study examined vocational health services students’ perceived knowledge, anxiety, hope, adaptation, and perspectives regarding the use of artificial intelligence in healthcare and evaluated whether these scores differed according to selected individual and health-related characteristics. A cross-sectional, descriptive, and correlational design was used. The study included 174 students enrolled at Batman University Vocational School of Health Services during the 2025–2026 academic year. Data were collected between April and May 2026 using a Personal Information Form and the Knowledge, Attitudes, and Perspectives Scales on the Use of Artificial Intelligence in Healthcare. Descriptive statistics, independent-samples t tests, Pearson correlation analysis, and Cronbach’s alpha coefficients were used. Internal consistency coefficients ranged from 0.777 to 0.897. No statistically significant differences were found according to gender, year of study, chronic illness status, or living arrangement. Students who regularly used medication had higher anxiety scores in the unadjusted analysis; however, this difference did not remain significant after Holm adjustment and was considered exploratory. Positive correlations were identified among all measured dimensions, with the strongest association observed between hope and adaptation. The findings indicate that students’ evaluations of artificial intelligence involve interrelated perceptions of knowledge, anxiety, positive expectations, and educational preparation needs. Healthcare education programs should include structured content addressing the clinical applications, limitations, ethical implications, and critical evaluation of artificial intelligence.